Exploration of Key Success Factors for Community Based Sustainable Halal Tourism Development and Its Impact on the Economy and Socio-Culture of Communities at Halal Tourism Objects in Riau - Darmawan Tya Indrajaya; Wali Saputra (Universitas Islam Darul 'ulum Lamongan, 2026)
This study aims to examine and analyse the effect of the provision of quality halal products, the provision of halal accommodation, local government support, halal travel services, halal recreation and entertainment facilities, the participation of local communities, on the development of people-based sustainable halal tourism and its implications on the economic, social, and cultural sustainability of local communities located in the area of tourist attractions in Riau. The data in this study used primary and secondary data. Primary data were collected through questionnaires and secondary data were obtained from tourist attraction reports from the ministry of tourism and creative economy and the website of the tourism office in Riau. This research was conducted on halal tourism objects in Riau with the local community as the unit of analysis. The research method used is the explanatory survey method while data testing uses the SEM - PLS method. The research findings show that the provision of qualified halal products, local government support, halal tourist travel services, halal recreation and entertainment facilities, and the participation of local communities affect the community based sustainable halal tourism development. Then, the community based sustainable halal tourism development has positive implications for the economic, social and cultural sustainability of local communities. Furthermore, the provision of qualified halal products, local government support, halal travel services, halal recreation and entertainment facilities, the participation of local communities indirectly affect the economic, social, and cultural sustainability of local communities through the community based sustainable halal tourism development. Especially for the provision of halal accommodation has no effect either directly on the community based sustainable halal tourism development or indirectly on the economic, social, and cultural sustainability of local communities.